KALINE BUTHEK WETENGE WAREG: Kajian Etika Berdasarkan al-Qur’an Hadis - Mochammad Ady Fairuzabadi (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2024)
This research examines river pollution river pollution due to batik waste in Setu River, Buaran, Pekalongan, symbolized by the expression “Kaline Buthek Wetenge Wareg”. through the expression “Kaline Buthek Wetenge Wareg”. Batik waste, which is rich in harmful chemicals such as BOD and COD, causes ecosystem damage and threatens public health. ecosystem damage and threatens public health. In Islam, the concept of maintaining cleanliness as part of faith is very relevant to tackle this problem. The Qur'an and hadith-based approach underscores the importance of environmental cleanliness and collective responsibility. environment as well as collective responsibility. This study recommends the adoption of environmentally friendly waste treatment technologies and policies that support sustainability. Further research is proposed to assess the impact of sewage on long-term health and ecosystems.